Personality Traits in Burning Mouth Syndrome Patients With and Without a History of Depression - Tu, Trang Thi Huyen; Watanabe, Motoko; Suga, Takayuki; Hong, Chaoli; Takao, Chihiro; Takenoshita, Miho; Motomura, Haruhiko; Toyofuku, Akira (Frontiers in Psychiatry, 2021)
Objectives So far, the strong link between neuroticism, chronic pain and depression has been well-documented in literatures. Some suggested they might share etiological factors and thus resulting in overlapping constructs. However, such effect has never been tested in Burning mouth syndrome (BMS) patients, a complex phenomenon influenced by both neuropathic and psychopathological factors. We aim to clarify how personality affects individual’s pain and pain-related experiences. Methods Two hundred forty-eight patients with BMS provided demographic information, psychiatric history; completed Ten-Items-Personality-Inventory, a visual analogue scale of pain, McGill-Pain-Questionnaire and adequate parameters of depressive state, catastrophizing thinking and central sensitization. Results BMS patients with depression history suffered more severe clinical symptoms; and scored higher in neuroticism, less in openness and extraversion compared to those without psychiatric diagnoses. Controlling for age, sex and duration of pain, neuroticism in BMS patients with depression correlates with affective dimension of pain. Instead, if psychiatric history is absent, neuroticism correlates with sensory dimension and pain intensity. In both groups, higher neuroticism, unlike other personality facets, contributed to a more severe clinical condition. Conclusion BMS patients with history of depression appear to have personality profiles different from group without psychiatric history. Of the 5 traits, neuroticism appears to be the most crucial dimension associated with the pain symptoms and patient’s conditions. This study implies that management of BMS must extend beyond solely providing pain-relieving medication and require additional psychotherapeutic approach.